2021
DOI: 10.3390/plants10020373
|View full text |Cite
|
Sign up to set email alerts
|

Detecting Genetic Mobility Using a Transposon-Based Marker System in Gamma-Ray Irradiated Soybean Mutants

Abstract: Transposable elements (TEs)—major components of eukaryotic genomes—have the ability to change location within a genome. Because of their mobility, TEs are important for genome diversification and evolution. Here, a simple rapid method, using the consensus terminal inverted repeat sequences of PONG, miniature inverted-repeat transposable element (MITE)-Tourist (M-t) and MITE-Stowaway (M-s) as target region amplification polymorphism (TE-TRAP) markers, was employed to investigate the mobility of TEs in a gamma-i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 53 publications
0
6
0
Order By: Relevance
“…The activity of transposable elements could be activated by a variety of stresses, such as gamma irradiation [ 63 , 64 , 65 ]. Hung et al [ 66 ] applied a transposon-based marker system to reveal abundant dynamic and active mobility levels of transposons in gamma-ray irradiated soybean mutant lines. Sen et al [ 67 ] detected retrotransposon insertional variations in drought-tolerant wheat mutants obtained by gamma ray irradiation and found high polymorphisms of retrotransposons microsatellite amplified polymorphism (REMAP) markers and inter-retrotransposon amplified polymorphism (IRAP) markers.…”
Section: Discussionmentioning
confidence: 99%
“…The activity of transposable elements could be activated by a variety of stresses, such as gamma irradiation [ 63 , 64 , 65 ]. Hung et al [ 66 ] applied a transposon-based marker system to reveal abundant dynamic and active mobility levels of transposons in gamma-ray irradiated soybean mutant lines. Sen et al [ 67 ] detected retrotransposon insertional variations in drought-tolerant wheat mutants obtained by gamma ray irradiation and found high polymorphisms of retrotransposons microsatellite amplified polymorphism (REMAP) markers and inter-retrotransposon amplified polymorphism (IRAP) markers.…”
Section: Discussionmentioning
confidence: 99%
“…TRAP method is useful for germplasm genotyping and producing markers associated with desirable agronomic traits in mutation breeding. Hung et al [50] employed this simple rapid method by using the consensus terminal inverted repeat sequences of PONG, miniature inverted-repeat transposable element (MITE)-Tourist (M-t) and MITE-Stowaway (M-s) as target region amplification polymorphism (TE-TRAP) markers to investigate the mobility of TEs in a gamma-irradiated soybean mutant pool. They concluded that MITEs were significant enough to confirm their practical utility as molecular markers for investigating mutant populations which were induced by random variations caused through physical mutagenesis (X-ray or gamma-ray).…”
Section: Present Applications Of Mutation Breeding In Soybeanmentioning
confidence: 99%
“…We previously created a mutant diversity pool (MDP) comprising 208 mutant soybean lines from seven wild-type cultivars that were irradiated with 60 Co gamma rays (250 Gy). We subsequently performed target region amplification polymorphism (TRAP) and transposable element (TE)-TRAP marker analyses to clarify genetic associations as well as gene expression and GWAS analyses of agronomic traits and phytochemical contents using our MDP and selected a soybean mutant with high isoflavone contents (average of 7,351 μg g −1 over a 3-year period) [ 51 53 ]. Because there has been relatively little breeding for isoflavone contents, a QTL analysis was conducted using only a few varieties (e.g., Angora, Luheidou2, Wayao, and Zhongdou 27) with isoflavone contents of 2,246–3,791 μg g −1 as the parental plants [ 30 , 37 , 39 , 54 ].…”
Section: Introductionmentioning
confidence: 99%